1991
DOI: 10.1136/hrt.65.2.77
|View full text |Cite
|
Sign up to set email alerts
|

Overnight studies in severe chronic left heart failure: arrhythmias and oxygen desaturation.

Abstract: Overnight studies were performed in 10 patients with severe chronic left heart failure (New York Heart Association grades III and IV) without pulmonary disease and in eight controls. Transcutaneous oxygen (Po2) and carbon dioxide tensions (Pco2) and oxygen saturation were measured and the electrocardiogram was recorded. During sleep mean oxygen saturation fell to 92-7% (minimum 86-1%) from 95-1% when awake. During the night oxygen saturation was below 95% for 62% of the time, below 90% for 6% of the time, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 35 publications
1
13
1
Order By: Relevance
“…The association between CSR at night, episodes of O 2 desaturation, and arrhythmogenesis in CHF has been documented. 3 Because sleep studies were not routinely performed, we do not know how many patients also exhibited classic CSR with episodes of hypoxemia at night and whether this was a cause of the higher incidence of nonsustained ventricular tachycardia. However, in the present study, compared with PB, a CSR-like pattern was not associated with any further increase in the complexity and severity of ventricular arrhythmias, suggesting that the occurrence of cyclical breathing pattern (either genuine PB or CSR-like) may be a marker of an increased risk of ventricular tachycardia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between CSR at night, episodes of O 2 desaturation, and arrhythmogenesis in CHF has been documented. 3 Because sleep studies were not routinely performed, we do not know how many patients also exhibited classic CSR with episodes of hypoxemia at night and whether this was a cause of the higher incidence of nonsustained ventricular tachycardia. However, in the present study, compared with PB, a CSR-like pattern was not associated with any further increase in the complexity and severity of ventricular arrhythmias, suggesting that the occurrence of cyclical breathing pattern (either genuine PB or CSR-like) may be a marker of an increased risk of ventricular tachycardia.…”
Section: Discussionmentioning
confidence: 99%
“…1 The episodes of apnea with concomitant hypoxemia and arousal, which are characteristic features of CSR, may be associated with increased sympathetic activity and precipitate ventricular arrhythmias. 2,3 A similar pattern of respiration during the daytime has been recently related to a poor outcome. 4 Patients with compensated CHF also demonstrate an oscillatory breathing pattern characterized by cyclical rises and falls in ventilation without true periods of apnea (periodic breathing [PB]).…”
mentioning
confidence: 99%
“…These facts, especially those related to the development of arrhythmias and the deterioration of ventricular function could have as pathophysiological bases the autonomic imbalance, hypoxia, hypercapnia, and the increase in the sympathetic amines, therefore aggravating neurohormonal disorders, especially in regard to the elevated levels of catecholamines 10,24 . In regard to the clinical, laboratory, and evolutional findings of the individuals studied, the breathing patterns and the characteristics of V-RR were independent of functional class, the cause of left ventricular global systolic dysfunction, and the magnitude of the changes in the echocardiographic parameters.…”
Section: Breathing Patternsmentioning
confidence: 99%
“…In approximately 50% of the individuals with left ventricular global systolic dysfunction, the presence of abnormal patterns of breathing can be identified. In these individuals, oscillatory patterns of breathing (oscillatory breathing) can be observed both during sleep and during wakefulness, and are characterized by successive periods of tachy/hyperpnea followed by brady/hypopnea, and, eventually, apnea [2][3][4][5][6][7][8][9][10] . Of the types of oscillatory breathing of clinical significance, Cheyne-Stokes respiration and periodic breathing stand out.…”
mentioning
confidence: 99%
“…The possible relationship between nocturnal oxygen desaturation and arrhythmias and sudden death in heart failure patients was suggested 20 years ago (Davies et al, 1991). More recently, Gami et al (2005) reported that sudden cardiac death in almost half of 78 heart failure patients with OSA occurred during sleeping hours from midnight to 6:00 a.m., significantly deviating from the typical time of death during early morning waking hours (6:00 a.m. to noon).…”
Section: Bradyarrhythmiasmentioning
confidence: 99%